A case study on classroom design of a selected SPED School for children with Attention Deficit Hyperactivity Disorder (ADHD) in relation to their behavior and activities - Blanco, Rosaleen Myra P. (UP College of Home Economics, 2012)
The study aimed to determine the relationship between the design of the classroom with students with Attention Deficit Hyperactivity Disorder (ADHD) and their class activities and the behaviour of the student with the said disorder. Briefly, ADHD is a psychiatric disorder that inhibits a person to control their behaviour. The respondent school was choses purposely as it meets the objective of the study. The study used the descriptive research design as interviews, photo documentation and observation were performed in gathering the required data. The findings show that the student with ADHD shows more enthusiasm and interest in activities that are more exciting and enjoyable. On the other hand, activities that require a lot of thinking and concentration cause less attention and tirinng for the student with the disorder. The findings also show that the existing design of the classroom stimulates the kind of activities performed by the student with ADHD in class; and these activities direct the actions of the student. Thus, the design of the classroom has an effect to the behaviour of the student with ADHD such as constantly running around the classroom, leaving of seat repetitively and losing focus on tasks. The study recommends designers to partake in projects and designing spaces that are used by persons with certain disorders. Also, for the government to further extend their role in serving the Filipinos who need more aid and attention to early intervene the challenging occurrences.